Are cardiac Magnetic Resonance Imaging and Radionuclide Ventriculography Good Options Against Echocardiography for Evaluation of Anthracycline Induced Chronic Cardiotoxicity in Childhood Cancer Survivors?. (1st April 2014) - Basar, Evic Zeynep; Corapcioglu, Funda; Babaoglu, Kadir; Anik, Yonca; Gorur Daglioz, Gozde; Dedeoglu, Reyhan
<x xml:space="preserve">Abstract</x> Anthracyclines are widely used for the treatment of solid tumors in pediatric oncology. However, their uses may be limited by progressive chronic cardiotoxicity related to the cumulative dosage. The aims of this study are to compare diagnostic techniques and prepare an algorithm for diagnosis of anthracycline induced chronic cardiotoxicity. The patients were evaluated according to age, sex, time elapsed since the last dose of anthracycline treatment, presence of cardiovascular symptoms, follow-up duration, type of anthracycline, cumulative anthracycline dose, and concomitant mediastinal radiation therapy. Late subclinical cardiotoxicity was detected by history, physical examination, electrocardiography (ECG), Holter monitor, echocardiography (ECHO), radionuclide ventriculography (MUGA), and cardiac magnetic resonance imaging (MRI). Thirty-seven male and 19 female patients with a median age of 11.2 ± 4.6 (range, 3.5–22.0) years were included in the study. Patients were grouped according to cumulative anthracycline doses. Subclinical cardiac dysfunction was detected in 20 patients by at least one of ECHO, MRI or MUGA after anthracycline chemotherapy. We revealed that other than ECHO, MRI and MUGA have high clinical importance for evaluating subclinical late cardiac complications in children treated with anthracyclines.